Assessing the Control Potential of Aldicarb against Grapevine Phylloxera - Loubser, J.T.; van Aarde, l.M.F.; Hoppner, G.F.J. (South African Journal of Enology and Viticulture, 2017)
Aldicarb 15 G soil treatments in vineyards were evaluated for their phylloxera control potential. A post-harvest application was made on single vines and phylloxera populations on roots were quantified using a washing and sieving technique. Natural population fluctuations on control vines were also determined. Data were subjected to a rank sum statistical test to determine the significance of the findings. Results indicated that aldicarb had a definite suppressing effect on all stages of grapevine phylloxera.